Does investor sentiment affect bank stability? International evidence from lending behavior. (May 2021) - Cubillas, Elena; Ferrer, Elena; Suárez, Nuria
Highlights: The paper studies the impact of investor sentiment on bank stability through lending. A sample of 2, 673 banks from 127 countries for the 1997–2016 period is analyzed. Periods of high sentiment reduce bank stability through lending. The impact is less negative with stronger creditor rights protection. The impact is less negative during episodes of systemic banking crises. Abstract: We study the impact of investor sentiment on bank credit and how changes in lending may affect bank stability. We analyze a sample of 2, 673 banks from 127 developed and developing countries during the 1997–2016 period. Our results indicate that periods of high investor sentiment positively affect bank lending and encourage bank risk-taking through the increase in the amount of loans granted which, in fact, reduces bank stability. We find that the impact of investor sentiment on bank stability through changes in growth in bank loans is less negative in countries where creditor rights protection is greater, in terms of both collateral and bankruptcy. During systemic banking crises, the negative effect on bank stability was weaker since any increase in bank credit supply provoked by investor sentiment was counteracted by the crisis.